2020
DOI: 10.31234/osf.io/xazdw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Looking the same, but remembering differently: Preserved eye-movement synchrony with age during movie-watching

Abstract: Naturalistic stimuli (e.g., movies) provide the opportunity to study lifelike experiences in the lab. While young adults respond to these stimuli in a highly synchronized manner (as indexed by intersubject correlations [ISC] in their neural activity), older adults respond more idiosyncratically. Here, we examine whether eye movement synchrony (eye-ISC) also declines with age during movie-watching and whether it relates to memory for the movie. Our results show no age-related decline in eye-ISC, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…For example, films have motion, which captures attention (Abrams & Christ, 2003;Mital et al, 2010), but static scenes and texts do not. In addition, highly produced films, like the ones used in previous studies that found evidence of the Tyranny of Film (Davis et al, 2021;Hutson et al, 2017;Loschky et al, 2015), may contain film-specific features such as cuts, close-ups, and foregrounding of objects in the center of the screen, that exert strong bottom-up control on eye movements (Dorr et al, 2010;Loschky et al, 2015;Smith, 2012;Tatler, 2007). Thus, the Tyranny of Film may be due to unique characteristics present in Hollywood films.…”
Section: Top-down Effects On Eye Movementsmentioning
confidence: 90%
See 4 more Smart Citations
“…For example, films have motion, which captures attention (Abrams & Christ, 2003;Mital et al, 2010), but static scenes and texts do not. In addition, highly produced films, like the ones used in previous studies that found evidence of the Tyranny of Film (Davis et al, 2021;Hutson et al, 2017;Loschky et al, 2015), may contain film-specific features such as cuts, close-ups, and foregrounding of objects in the center of the screen, that exert strong bottom-up control on eye movements (Dorr et al, 2010;Loschky et al, 2015;Smith, 2012;Tatler, 2007). Thus, the Tyranny of Film may be due to unique characteristics present in Hollywood films.…”
Section: Top-down Effects On Eye Movementsmentioning
confidence: 90%
“…To simulate real world experiences in the current experiment, we used short films of naturalistic activities that excluded many of the standard film editing techniques present in Hollywood style films. Thus, we hypothesized that the videos in the current study may afford a stronger influence of top-down processing on attention than what has been used in previous work (Hutson et al, 2017;Loschky et al, 2015;Huff et al, 2017;Davis et al, 2021). Further, evidence of the Tyranny of Film has exclusively come from studies with young participants (see however, Davis et al, 2021).…”
Section: Top-down Effects On Eye Movementsmentioning
confidence: 93%
See 3 more Smart Citations